An analysis of the challenges encountered in administering Zimsec examinations: the case of Sherwood Munyati Cluster, Kwekwe District - Munyengeterwa, Melody (Midlands State University, 2019)
The point of this survey is to analyze the challenges being experienced in the administering of ZIMSEC examinations using the case of the Sherwood-Munyati cluster. To establish the ZIMSEC examinations related challenges faced by the cluster. The research’s objectives were to establish the origin of the examinations challenges faced by the cluster and to recommend the successful mitigation strategies for dealing with the ZIMSEC examinations related challenges for the cluster. This examination is going to utilize the quantitative research method. Stratified random sampling was utilised to come with the 15 respondents being 12 teachers and 3 headmasters. Questionnaires and interviews were the data collection tools used. The research’s major conclusions were that transport is a serious challenge to exams integrity in the cluster through delays, exposure and damage of exams material, exams cheating was on the increase in the cluster, leaking of examinations was now a rampant problem in Zimbabwe. Pursuant to these conclusions the researcher recommended the enforcement of ethical standards through stiffer penalties to offenders. There may be need to amend the relevant pieces of legislation to ensure that deterrent sentences are meted out to the culprits. Formation of student intelligent committees. As previously highlighted these help in the detection and reporting of cases of exams leakages in the cluster. This should be embraced at the national level with rewards being offered for leakage syndicates busters. And lastly, provision of transport and security personnel by ZIMSEC. ZIMSEC is an independent exams body that should fight to ensure that its integrity is upheld at all costs. Suffice to say that central to the pursuit of this is exams security. With Zimbabwe highly celebrated literacy levels, ZIMSEC should by now an exams body for the whole region if not Africa as a whole.